Development of novel photonic switching devices based on low-dimensional carbon nanostructures for compact pulsed lasers - Choi, Sun Young (The Graduate School, Ajou University, 2015)
Low-dimensional carbon nanostructures such as carbon nanotubes (CNTs) and graphene have been among the most interesting materials studied in recent decades. The inherently fast response time, broadband linear absorption, and third-order nonlinearity of singlewalled CNTs (SWCNTs) and graphene enable the application of these materials as ultrafast broadband optical-switching devices, such as saturable absorbers (SAs). Owing to the superior properties of carbon-nanostructure-based SAs, excellent mode-locking performance has been demonstrated compared with the results achieved using conventional semiconductor saturable absorber mirrors (SESAMs). Compared with SESAMs, carbon nanostructures are more flexibly applied as SAs. To date, SWCNT and graphene are the most frequently used SAs for ultrafast pulsed lasers. However, despite the substantial results regarding carbon-nanostructure-based SAs, research on the broadband application and engineering of SA parameters, e.g., the linear and nonlinear absorption properties, has not yet been conducted. In this thesis, the linear and nonlinear properties of SWCNT and graphene SAs are controlled by various approaches. The delicate handling of carbon-nanostructure materials leads to the uniform and low scattering losses of devices. By controlling the concentrations and thicknesses of the SWCNT-SAs on transparent or reflective substrates, the linear absorption of the devices can be modulated between less than 1% and over 30%. High-quality, largearea, single-layer graphene is also fabricated, and flake-based graphene is suggested to compensate for the limited gap of 2.3% intrinsic linear absorption per layer of the welldefined single-layer graphene. The nonlinear optical characterization of the parameter controlled carbon-nanostructure-based SAs is performed in the broadband spectral region. The fast recovery time of the devices is revealed for both the SWCNT and graphene SAs, indicating that nonlinear optical properties can be engineered by modulating the linear absorption of the devices using high-resolution nonlinear transmission measurements. According to the parameter engineering technique, a novel type of SA for the compact-fiber and bulk-laser system is suggested, including an all-in-one multifunctional SA mirror. The varying thickness of the carbon-nanostructure SA on asymmetry structured platform, polarization-dependent, evanescent field-coupled optical properties of the devices are controllable. Material-injected fibers are also developed, for a robust and relatively long nonlinear evanescent wave interaction in the fiber-laser system. Furthermore, sub-cm waveguides are proposed for the device integration. These multifunctional, novel carbonnanostructure- based SAs have been demonstrated for fiber and bulk solid-state laser modelocking and ultra-compact waveguide laser Q-switched operations. Evanescent-waveinteraction- type SWCNT and graphene-injected holey fibers exhibit a robust and relatively high power operation compared with previous carbon-nanostructure-based SAs. The application of an all-in-one SA on a single dielectric mirror is successfully demonstrated, whereby the 30-cm-long laser cavity generates 150-fs pulses. The Q-switching operation of the channel waveguide laser is also achieved using a modulation-depth-controlled SWCNTSA mirror. Total length of 1-cm-long laser cavity with an SWCNT-coated output coupler exhibits a stable Q-switched pulse generation; this is basic research for SWCNT and graphene-based SA-mode-locked ultra-compact waveguide lasers.
학위논문(박사)--아주대학교 일반대학원 :에너지시스템학과,2015. 2
Keywords: low-dimensional carbon nanostructure; saturable absorber; pulsed laser; compact laser